Bartonella Infection in Animals: Carriership, Reservoir Potential, Pathogenicity, and Zoonotic Potential for Human Infection - Breitschwerdt, Edward B. (American Society for Microbiology, 2000)
Recent observations have begun to support a role for Bartonella spp. as animal as well as human pathogens. Bartonella spp. are vector-transmitted, blood-borne, intracellular, gram-negative bacteria that can induce prolonged infection in the host. Persistent infections in domestic and wild animals result in a substantial reservoir of Bartonella organisms in nature that can serve as a source for inadvertent human infection. The prevalence of bacteremia can range from 50 to 95% in selected rodent, cat, deer, and cattle populations. Dogs infected with Bartonella spp. can develop lameness, endocarditis, granulomatous lymphadenitis, and peliosis hepatis, lesions that have also been reported in association with human infection. Understanding the role of Bartonella spp. as pathogens in cats and other wild or domestic animals awaits the results of additional studies. Considering the extensive animal reservoirs and the large number of insects that have been implicated in the transmission of Bartonella spp., both animal and human exposure to these organisms may be more substantial than is currently believed.